MIMOS 2020 Jossi Wieler - Gilardi, Paola; Fournier, Anne; Klaeui, Andreas; Schmidt, Yvonne (MIMOS - Schweizer Jahrbuch Darstellende Kuenste, 2021)
As one of the defining theatre and opera directors in the German-speaking world, Jossi Wieler has developed his signature style by creating ideas through dialogue and dissecting works for their socio-political relevance for present-day audiences. In this volume, a range of voices shed light on his working methods, the significance of reciprocal inspiration in the creative process and the ethics of his aesthetic.